Landsat 8 Observation of the Internal Solitary Waves in the Lombok Strait - I Wayan Gede Astawa Karang; Chonnaniyah Chonnaniyah; Takahiro Osawa (Faculty of Geography, Universitas Gadjah Mada, 2019)
Landsat 8, Landsat Data Continuity Mission (LDCM) satellite, was launched on 11 February 2013 with Operation Land Imager (OLI) sensors. Tis sensor has better radiometric performance than the previous mission, which is quantized in the 12-bit dynamic range due to an increase in the signal-to-noise (SNR) ratio. In this analysis, the spatio-temporal distribution of the propagation of the internal solitary wave (ISW) in the Lombok Strait was extracted from the Landsat 8 images described for the ﬁrst time. Tere were 14 ISW events studied for period 2014 - 2015 using Landsat 8. Te manifestations of ISW recorded on Landsat 8 images were then extracted using digitization method to investigate and measure several parameters and ISW distribution in the Lombok Strait. Te estimation results of the average ISW phase velocity in this study are 2.05 ms-1 with the direction of propagation heading north at an average angle of 19.08°. Tis study has shown that Landsat 8 can be used to monitor and analyze several internal wave parameters in the ocean.